2015
DOI: 10.1016/j.paid.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and subsequent disruptive behavior in school: The protective functions of anger regulation coping

Abstract: Peer victimization is linked to adjustment problems in youth, including aggressive behavior, yet not all victimized youth are aggressive. The present study investigated whether youth’s anger regulation coping might attenuate the positive association between peer victimization and subsequent aggressive behavior. Longitudinal data from 485 7th-grade students (55% female, mean age = 12.84 years) and their teachers were collected in the fall and six months later. Teacher ratings of youth aggressive behavior at fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Several research studies have explored the relationship between victimization, including peer violence, and both behavioral consequences and emotional adjustment. Results have suggested that many youths will exhibit subsequent internalizing symptoms and disruptive behavior in response to patterns of violent events [1,2,3]. With regard to exposure to violence, many youths are the primary witnesses to criminal activity in disadvantaged settings, while peer violence and other forms of direct victimization remain prevalent primarily among those between the ages of 12–18 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have explored the relationship between victimization, including peer violence, and both behavioral consequences and emotional adjustment. Results have suggested that many youths will exhibit subsequent internalizing symptoms and disruptive behavior in response to patterns of violent events [1,2,3]. With regard to exposure to violence, many youths are the primary witnesses to criminal activity in disadvantaged settings, while peer violence and other forms of direct victimization remain prevalent primarily among those between the ages of 12–18 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was observed in another stuy that anger management was protective against peer bullying among adolescents and that it decreased hostile behaviors (32).…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of similar-aged children, expressions of anger were associated with increased peer victimization experiences (Camodeca & Goossens, 2005), and children who demonstrated the ability to regulate their anger experienced fewer instances of peer victimization Kaynak et al, 2015). Additionally, in longitudinal studies among younger children, deficits in regulating anger were associated with peer victimization experiences , and anger served as a risk factor for subsequent peer victimization .…”
Section: Theoretical Implicationsmentioning
confidence: 95%
“…Even in situations when children were asked to recount experiences of peer victimization, children who experienced more peer victimization demonstrated more sympathetic nervous system reactivity (Kliewer, Dibble, Goodman, & Sullivan, 2012), negative affect (Bollmer et al, 2006), and emotional distress (Rosen et al, 2012). Given that children who effectively regulate their emotions are less likely to be victimized by their peers (Kaynak, Lepore, Kliewer, & Jaggi, 2015), effective emotion regulation and conflict resolution skills appear critical for reducing the frequency with which children experience peer victimization (Kochenderfer-Ladd, 2004).…”
Section: Emotion Regulation and Peer Victimizationmentioning
confidence: 99%